THE PRINCIPLE OF SELF SUBMISSION IN DIVORCES CASES FROM THE PERSPECTIVE OF LEGAL CERTAINTY - Uthlufah, Haqqiyah (Faculty of Law Universitas Trunojoyo Madura, 2020)
The problem of the principle of submission in the divorce law in the Religious Court by a non-Muslim couple occurs because the couple's marriage is based on Islamic law. What cannot be separated from Islamic law is Islamic family law because it is related to the faith of a Muslim. Islamic family law can only apply to Muslims and cannot apply to non-Muslims. The problem of the principle of submission to the divorce law was incomplete (incomplete norm) or the existence of a legal vacuum (vacuum of norm) in marriage law in Indonesia. This research is a legal research and is normative in nature. The approach used is statutory, case, and conceptual. The legal materials used are primary, secondary and tertiary. The method of collecting legal materials is first to qualify the facts and then to qualify the law. The analytical tool used is legal interpretation in the form of principal, systematic and grammatical interpretation.